Development of intron length polymorphism markers in genes encoding diketide-CoA synthase and curcumin synthase for discriminating Curcuma species. (1st March 2016) - Kita, Tomoko; Komatsu, Katsuko; Zhu, Shu; Iida, Osamu; Sugimura, Koji; Kawahara, Nobuo; Taguchi, Hiromu; Masamura, Noriya; Cai, Shao-Qing
Graphical abstract: Highlights: We developed new method for discriminating Curcuma species by ILP markers. Seven Curcuma species were clearly distinguishable by applying this method. C. longa specimens were geographically distinguishable. C. kwangsiensis and C. wenyujin, with the same trn K sequence, could be identified. Our method is a potential tool for global classification of the genus Curcuma . Abstract: Various Curcuma rhizomes have been used as medicines or spices in Asia since ancient times. It is very difficult to distinguish them morphologically, especially when they are boiled and dried, which causes misidentification leading to a loss of efficacy. We developed a method for discriminating Curcuma species by intron length polymorphism markers in genes encoding diketide-CoA synthase and curcumin synthase. This method could apply to identification of not only fresh plants but also samples of crude drugs or edible spices. By applying this method to Curcuma specimens and samples, and constructing a dendrogram based on these markers, seven Curcuma species were clearly distinguishable. Moreover, Curcuma longa specimens were geographically distinguishable. On the other hand, Curcuma kwangsiensis (gl type) specimens also showed intraspecies polymorphism, which may have occurred as a result of hybridization with other Curcuma species. The molecular method we developed is a potential tool for global classification of the genus Curcuma .